1997
DOI: 10.5153/sro.109
|View full text |Cite
|
Sign up to set email alerts
|

Users and Social Science Research: Policy, Problems and Possibilities

Abstract: Recent times have seen a significant reorientation in public funding for academic research across many countries. Public bodies in the UK have been at the forefront of such activities, typically justified in terms of a need to meet the challenges of international competitiveness and improve quality of life. One set of mechanisms advanced for further achieving these goals is the incorporation of users' needs into various aspects of the research process. This paper examines some of the consequences of greater us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Researchers especially have been trained to think that one of the primary advantages of the academic system is its ability to support independent research conducted at arm's length from other competing in uences that might jeopardize research quality and direction. 11 Although our study revealed two situations in which there was disagreement (admittedly resolved by the researchers having the nal say), we did not uncover concerns about the quality of the research precipitated by decision-maker involvement. On the contrary, in some situations the decision-maker partner was perceived to have injected a new kind of rigour into the process, a sort of ongoing healthy self-consciousness about the contextual implications of the research.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Researchers especially have been trained to think that one of the primary advantages of the academic system is its ability to support independent research conducted at arm's length from other competing in uences that might jeopardize research quality and direction. 11 Although our study revealed two situations in which there was disagreement (admittedly resolved by the researchers having the nal say), we did not uncover concerns about the quality of the research precipitated by decision-maker involvement. On the contrary, in some situations the decision-maker partner was perceived to have injected a new kind of rigour into the process, a sort of ongoing healthy self-consciousness about the contextual implications of the research.…”
Section: Discussionmentioning
confidence: 60%
“…As new directions for fostering greater use of applied research are developed, universities, research funders, researchers, and to some extent decision-makers, will increasingly need to recognize and support these activities 'as part of the ''real'' work of research'. 11 Our respondents (especially researchers) stressed the extensive time and effort required to facilitate engagement activities between researchers and decisionmakers. They also noted that these costs are not adequately recognized either generally by the academic system (including universities and research funders) or by individual researchers in their planning of the research process, observations which have been repeatedly recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Such consequent trends-what Delanty (2001) calls the "new managerialism" or "academic Taylorism"-have occurred for universities all over the world: for example, they have been noted by authors in the United States (Lynton and Elman 1987), Canada (Abu-Laban 1989), Australia (Trotman and Robertson 1992), Britain (Bridges 1998), andMexico (Ibarra-Colado 2001). For some scholars, Mode 2 has led to a loss of traditional academic autonomy-the end of the tenure system, the promotion of scholarship that is geared toward satisfying customer demand over disciplinary needs or individual curiosity (Rappert 1997;Trotman and Robertson 1992); for others, it has resulted in an uncomfortable disjunction between the new expectations and the old discipline-driven modes of work, including the persistence of discipline-based criteria for reward and advancement (Lynton and Elman 1987).…”
Section: The University In Contextmentioning
confidence: 99%
“…If services are to be developed, and standards set and maintained, then people's lives and experiences of services must be fully understood. Moreover, within the broader policy context that stresses the involvement of service users in the formulation of policy and practice (Secretary of State for Health 2000a,b), there needs to be active engagement with people's views on service improvements (Rappert 1997). In the UK, the Health and Social Care Act 2001, which came into force in 2003, places a duty on services to consult with users before any changes are made to services (Her Majesty's Government 2001).…”
Section: Introductionmentioning
confidence: 99%